PENERAPAN MODEL TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Ni Ketut , Erawati; Ni Made , Ayu Sentia Devi; I Wayan, Suwiyasa (Emasains : Jurnal Edukasi Matematika dan Sains, 2024)
This study aims to improve the mathematics learning outcomes of tenth-grade students at SMA Negeri 6 Denpasar through the implementation of the Team Assisted Individualization (TAI) model in trigonometry. The research methodology utilized is classroom action research, involving collaboration between teachers and students. The steps of Team Assisted Individualization (TAI) are integrated into the teaching process, where students work in small teams to assist each other in understanding trigonometric concepts. Classroom action research is conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. Student learning outcomes data are obtained through formative tests and observations during the learning process. The research results are expected to provide insights into the effectiveness of the Team Assisted Individualization (TAI) model in enhancing the understanding and academic achievement of tenth-grade students at SMA Negeri 6 Denpasar in trigonometry. The implications of this research are anticipated to contribute positively to the development of innovative and student-oriented mathematics teaching methods.